Guía para la creación de un festival internacional de publicidad. Caso industria ecuatoriana de publicidad - Jaramillo Dahik, José Miguel (2014)
This project was undertaken to complete the advertising career and discusses the development of a methodological guide for the implementation of an international advertising festival made in Ecuador. Based on interviews with the major players in the Ecuadorian advertising industry. The aim of this work is the development of a methodological guide, in the future to contribute effectively in developing an advertising contest, attractive for the major advertising professionals inside and outside the country. In addition to outline some processes for developing creative advertising materials, and methods used to weigh, measure and value the advertising creativity, in order to provide bibliographic support to future research on the subject. The research process used as reference tools: Preliminary Exploration to search theoretical and methodological background of the topics, depth interviews, literature research and information pulled from the Internet. When the investigation process concluded, the parameters that the festival needs to meet are devised and some factors specified in order to know the method that the competion could use to judge creativity.